2021
DOI: 10.1088/1402-4896/ac4192
|View full text |Cite
|
Sign up to set email alerts
|

Band structures and topological properties of twisted bilayer MoTe2 and WSe2

Abstract: We calculate the electronic band structures and topological properties of twisted homobilayer transition metal dichalcogenides(t-TMDs), in particular, bilayer MoTe2 and WSe2 based on a low-energy effective continuum model. We systematically show how the twist angle, vertical electric field and pressure modify the band structures of t-TMDs, often accompanied by topological transitions.We find the variation of topological transitions mainly take place in a limited range of parameters. The electric field can effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…The most prominent examples are twisted bilayer and trilayer graphene, exhibiting magnetism and superconductivity due to strong correlations . Other platforms for correlated physics are offered by twisted TMDCs [100][101][102] and twisted CrI 3 mono-and bilayers [103,104]. Regarding proximity effects, a recent study shows the sensitivity of the spin polarization, magnetic anisotropy, and Dzyaloshinskii-Moriya interaction on the twist angle in graphene/2H-VSeTe heterostructures [105].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent examples are twisted bilayer and trilayer graphene, exhibiting magnetism and superconductivity due to strong correlations . Other platforms for correlated physics are offered by twisted TMDCs [100][101][102] and twisted CrI 3 mono-and bilayers [103,104]. Regarding proximity effects, a recent study shows the sensitivity of the spin polarization, magnetic anisotropy, and Dzyaloshinskii-Moriya interaction on the twist angle in graphene/2H-VSeTe heterostructures [105].…”
Section: Introductionmentioning
confidence: 99%
“…The reason why we choose 1 °is that the bandwidth of the first flat band increases with the increase of twist angle [54]. In order to obtain an extremely narrow bandwidth, we choose 1 °angle here.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…[20][21][22][23] These novel quantum states originate from the formation of flat electronic bands near a magic twisted angle (∼ 1 ∘ ) under the influence of the moiré superlattice. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Such flat bands exhibit a sensitive dependence on small lattice deformations [24,38] that are induced by lattice relaxation or strain. On the other hand, strain is an effective tool for engineering the flat bands [24,39] and thus helps us understand the various exotic quantum states in TBG.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental [8] and theoretical works [24,36,[39][40][41] have shown that applying a heterostrain (relative strains between layers) in a two-layer structure can significantly modify the band structures and electronic phases. Due to the interaction between substrate and graphene in the preparation process, various strains are prevalent in actual TBG samples.…”
Section: Introductionmentioning
confidence: 99%